A (p)review: Adhesion of printcrete for tunnel structures - Yaxin Tao; Li Wang; Timothy Wangler; Karel Lesage; Geert De Schutter; Kim Van Tittelboom; Yong Yuan (Case Studies in Construction Materials)
The construction of tunnel structures is a labor-intensive and challenging process, particularly in extreme environments such as high geothermal zones or cold regions, where human presence is often unsuitable or even hazardous. These conditions call for innovative construction techniques that can minimize on-site human intervention. Digital fabrication with concrete, particularly through 3D concrete printing, presents a transformative potential for automating the construction of tunnel structures. Unlike conventional methods such as mold-casting or shotcrete, which inherently ensure good adhesion between the material and the rock substrate, extrusion-based printable concrete (printcrete) faces significant challenges in achieving satisfactory adhesion, especially during its fresh and early hardening stages. Adhesion performance is critical for the structural integrity of printed tunnel structures, and a deeper understanding of this aspect is necessary. To this end, this paper consolidates prior research, focusing on three interacting components influencing the adhesion: the substrate, the printcrete, and any bonding agent at the interface. Based on these studies, the paper further discusses the unique adhesion challenges encountered in tunnel construction using printcrete and presents potential solutions.